Uncovering the Underlying Causes of Severe Acute Hepatitis of Unknown Aetiology in Children: A Comprehensive Review - Maria AlShurman; Bara' Abdallah AlShurman; Hibah Sehar; Amy Evans; Tala Alzoubi; Christina Mac; Zahid Ahmad Butt (Dr. Sulaiman Al Habib Medical Journal)
Background Since October 2021, multiple paediatric cases of severe acute hepatitis of unknown aetiology (SAHUA) not caused by hepatitis A–E viruses have been reported by multiple countries. As of 14 September 2022, approximately 1296 probable cases of SAHUA in 37 countries and regions had been reported. Objectives The purpose of this study was to present a complete picture of this outbreak, including its origin, current cases, clinical signs, possible hypotheses, and potential treatments. Methods A thorough search for literature from October 2021 to September 2023 was performed in the PubMed and Medline databases. Additional websites, including the WHO, CDC, ECDC, and the UKHSA, were searched for further relevant data. Results Common clinical symptoms include jaundice, vomiting, pale stools, diarrhoea, abdominal pain, and nausea, whereas fever is infrequent. Elevated AST and ALT are prevalent, and most cases test positive for adenovirus. However, immunohistochemical staining on liver tissue often yields negative results for adenovirus, thus challenging the hypothesis that adenovirus is a definitive cause. A recent compelling hypothesis has implicated AAV-2 as a likely etiologic agent of SAHUA in paediatric cases involving abnormal AAV-2 replication products and immune-mediated hepatic disease. Evidence of low immunogenicity, tissue tropism, and immune responses supports this hypothesis. SARS-CoV-2's role has also been explored. Some SAHUA cases have SARS-CoV-2 IgG positivity even when PCR tests are negative, thereby suggesting silent prior infections. Cidofovir, a suggested treatment for severe human adenovirus infection in immunocompromised patients, has not decreased adenoviral load in two cases. Notably, 29 deaths have been reported, and 55 cases have required or received liver transplant. Conclusion SAHUA in children presents a complex challenge with potential involvement of AAV-2 and immune-mediated factors. SARS-CoV-2 may affect disease severity–a possibility warranting further investigation. Treatment options include diagnostics, supportive care, antivirals, and immunosuppression. Prevention relies on infection control measures, and management requires advanced diagnostics and international collaboration. SAHUA remains an enigma, thus underscoring the need for continued research and adaptability to emerging infectious threats.